Entre castelos, processos e metamorfoses : uma experiência urbana na Aracaju do presente - Lima, Laís Alves de Oliveira (2015)
The streets with its inhabitants, life forms emerge in an unpredictable daily although the regulation seeks uniformity and predictability for the experience. Walking on the plots of the city, searching for life forms that resist the logic wich prevent the proliferation of difference, a writing on subjectivity production in the city outlined. The writing was done through the experience of streets and discussions revolving around it, from the ethnography of urban space recorded in field diaries. The meetings were produced in the streets with residents, bystanders, people who make the street work camp. Contact with the metropolis, their relationships and multiplicity, revealed a moving field and led the look on possibilities of life that are carried in the gaps in a way there capitalistic into thinking such lives that resist as life-creating itself as works of Art. Franz Kafka appears there as the intercessor of a full metamorphoses of writing that seeks to narrate the tales lived in as Maria Feliciana, An Acrobatic Girl, The Bridge and The Soup People. From the experiences in the metropolis it was observed that more than conserving, life wants to expand, generating more life, impose themselves a new direction. Writing sought new ways of thinking about the present, creating escape routes for problems that arise in daily life. The path is open, discussions here are made of paths that seek to lead the eye on the present.